Antagonist peptides of human interferon-alpha2b isolated from phage display library inhibit interferon induced antiviral activity - Tian Wang; Bai Gang; Li Zheng-he; Yang Wen-bo (Acta Pharmacologica Sinica, 2016)
Aim: To screen human interferon (IFN)-α2b antagonist peptides from a phage displayed heptapeptide library. Methods: WISH cells and polyclonal anti-IFN-α2b antibodies were used to select IFN receptor-binding peptides from a phage displayed heptapeptide library. The specific binding of phage clones was examined by phage ELISA and immunohistochemistry. The specific binding activities of synthetic peptides to WISH cells were detected by competition assay. Effects of synthetic peptides to IFN-induced antiviral activity were analyzed by evaluating the cytopathic effect (CPE) using the MTT method. Results: Twenty-three positive clones were obtained after seven rounds of selection. Ten clones were randomly picked from the positive clones and were sequenced. The corresponding amino acid sequences suggested 3 groups homologous to the 3 domains of IFN-α2b, defined by residues 24–41, 43–49, and 148–158 of IFN-α2b. As they presented as corresponding to IFN receptor-binding domains, AB loop and E helix, clone No 26 and 35 were chosen for further characterization and shown to bind to WISH cells. Two peptides corresponding to clone No 26 and 35, designated SP-7(SLSPGLP) and FY-7(FSAPVRY) were shown to compete with GFP-IFN-α2b for binding to its receptor and to inhibit the IFN-α2b-induced antiviral activity. Conclusion: Both IFN-α2b antagonist peptides, SP-7 and FY-7, were able to inhibit the IFN-induced antiviral activity, and could be helpful in laying the foundation for the molecular mechanism of the interaction between IFN and its receptor.